Global assessment of vulnerability to sea‐level rise in topography‐limited and recharge‐limited coastal groundwater systems. Issue 4 (26th April 2013) - Michael, Holly A.; Russoniello, Christopher J.; Byron, Lindsay A.
Key Points Topography‐limited systems respond more to sea‐level rise than recharge‐limited 70% of world coastlines may be topography‐limited Hydrogeologic setting is critical to determine groundwater vulnerability